Disability after minor stroke and TIA: A secondary analysis of the SOCRATES trial. (13th August 2019) - Cucchiara, Brett; George, Donna Kurowski; Kasner, Scott E.; Knutsson, Mikael; Denison, Hans; Ladenvall, Per; Amarenco, Pierre; Johnston, S. Claiborne
Abstract : Objective: To examine factors associated with disability following TIA and minor stroke, including poststroke complications such as stroke recurrence, major bleeding, and other adverse medical events. Methods: The SOCRATES trial randomized patients with TIA/minor stroke (NIH Stroke Scale [NIHSS] score ⩽5) within 24 hours of onset. We performed a post hoc analysis of factors associated with disability (modified Rankin Scale [mRS] score >1). TIA and minor stroke were analyzed separately. Patients with premorbid mRS >0 were excluded. Results: At 90 days, 687/3, 663 (19%) patients with stroke were disabled; for TIA, 122/2, 384 (5%) were disabled. In multivariate analyses, age, diabetes, and NIHSS were associated with disability in the stroke cohort, and age with disability in the TIA cohort. Postrandomization events (recurrent stroke, myocardial infarction, major bleeding, serious adverse events) were strongly associated with disability in both cohorts (stroke cohort: odds ratio [OR] 5.6, 95% confidence interval [CI] 4.5–6.9; TIA cohort: OR 14.8, 95% CI 9.9–22.0). Of the TIA patients who ended up disabled, 65% experienced a postrandomization event; for stroke patients who ended up disabled, 39% had a postrandomization event. Disability increased linearly with NIHSS score ( p < 0.0001) and was greater in those with limb weakness ( p < 0.0001). Conclusions: After TIA and minor stroke, subsequent stroke and medical complications are strongly associated with disability. In addition, even within a low range of baseline scores, the NIHSS is a powerful predictor of disability in minor stroke patients, with items scoring limb weakness particularly associated with subsequent disability.